Theology and families - Thatcher, Adrian (Challenges in contemporary theology, 2007)
Beginning with real families and children -- The Bible in the service of families -- The teaching of Jesus about families and children -- Relations, families, and the triune God -- Spouses and partners -- Children, parents, and rights -- God, parents, and children -- Open families : choosing to be childless -- Families and the domestic church.